Spectroscopic study of five SB1 stars with CP components. Issue 3 (10th August 2022) - Catanzaro, G; Colombo, C; Ferrara, C; Giarrusso, M
ABSTRACT: In this paper, we present the results of a spectroscopic campaign devoted to ascertaining the actual nature of a sample of five objects reported as chemically peculiar stars in the Catalogue of Ap, HgMn and Am stars (2009, A&A, 498, 961). Spectroscopic observations were obtained with Catania Astrophysical Observatory Spectropolarimeter. For each of the objects, we derive the effective temperature, gravity, rotational and radial velocities, and chemical abundances using the spectral synthesis method. All the targets were found to be SB1 systems. Our abundance analysis led us to classify HD 40788 and HD 187959 as marginal Am stars and HD 202431 as an Am star, and to confirm HD 134793 as an SrEuCr Ap star and, finally, HD 189652 as a normal star. Finally, we confirm that Am stars can possibly be used as an accurate tool to date stellar populations in galaxies.